Comparison of Fluoroquinolones and Other Antibiotic Prophylaxis Regimens for Preventing Complications in Patients Undergoing Transrectal Prostate Biopsy - Gabriele Tulone; Sofia Giannone; Piero Mannone; Alessio Tognarelli; Tommaso Di Vico; Rosa Giaimo; Alessandro Zucchi; Marta Rossanese; Alberto Abrate; Nicola Pavan; Francesco Claps; Vincenzo Ficarra; et al. (MDPI AG, 2022)
Our study aimed to compare the incidence of infective complications after transrectal ultrasound-guided prostate biopsy (TRUSBx) when adopting different antimicrobial prophylaxis regimens. A multi-institutional cohort of 1150 patients who underwent TRUSBx was retrospectively analyzed. Procedures were performed between 2017 and 2019 (before and after the EMA warning about the use of fluoroquinolones for the antibiotic prophylaxis of patient candidates to TRUSBx). The primary endpoint was the occurrence of infective complications, including sepsis and/or fever. The population was stratified according to the antibiotic prophylaxis adopted: fluoroquinolones (levofloxacin, ciprofloxacin, prulifloxacin), cephalosporins (cefixime, ceftriaxone) or trimethoprim/sulfamethoxazole. Univariable and multivariable binomial logistic regression models were used to assess the odds ratio (OR) with 95% confidence interval (CI) testing of the risk of infective complication after adjusting for each prebiopsy covariate. In total, 478 (41.6%) patients received fluoroquinolone-based prophylaxis. Among these, 443 (38.5%), 25 (2.2%) and 10 (0.9%) patients received levofloxacin prophylaxis, ciprofloxacin and prulifloxacin, respectively while 14.6% received cefixime, 20.7% received the comedication of ceftriaxone/fosfomycin and 23.1% received trimethoprim/sulfamethoxazole. The trimethoprim/sulfamethoxazole and fluoroquinolone regimens were significantly associated with a lower risk of infective complications (OR 0.15, 95% CI 0.03-0.48, p = 0.003 and OR 0.17, 95% CI 0.06-0.43, p < 0.001, respectively). The ceftriaxone/fosfomycin (OR 0.21, 95% CI 0.04-0.92, p = 0.04) and fluoroquinolone (OR 0.07, 95% CI 0.00-0.70, p = 0.048) prophylaxis were associated with a lower risk of infective sequelae. Fluoroquinolone-based prophylaxis was associated with a lower risk of infective complications after TRUSBx compared to other prophylaxis regimens although its clinical application was recently forbidden by European Medical Agency restrictions.